Power consolidation with welfare designs? The emergence of old-age pensions in nondemocratic regimes around the world. Issue 2 (17th February 2022) - Grünewald, Aline
ABSTRACT: Old-age pensions are the most widespread social security programmes around the world that in many countries account for a huge part of the national budget. Based on the PENLEG dataset (Pension Legislation around the World, 1880–2010), this article answers the question whether the political regime type has affected the choice of a specific pension design when implementing old-age pensions for the first time. The global study shows that nondemocratic regimes were more likely to implement social insurance designs, as these pension designs are best suited to bind citizens to the state and to target benefits on groups that are essential for regime survival. In contrast, the study can only find weak evidence that electoral autocracies were less likely to implement social insurance designs than closed autocracies. Moreover, colonial legacies mattered strongly. Especially former French colonies were more likely to implement social insurance designs.